Language Teaching Research and Language Pedagogy. - Ellis, Rod R. (John Wiley & Sons, 2012)
This book examines current research centered on the second language classroom and the implications of this research for both the teaching and learning of foreign languages. It offers illuminating insights into the important relationship between research and teaching, and the inherent complexities of the teaching and learning of foreign languages in classroom settings. Offers an accessible overview of a range of research on instruction and learning in the L2 classroomBridges the relationship between research, teachers, and learnersHelps evolve the practice of dedicated current language teachers.